Abaka Han’ın darp ayları yazılı gümüş sikkeleri, M. 1265-1282 (H. 663-680) = Abaka Khan’s silver coinage that bear the date as well as the month in which they were struck. - Ender, Celil. (İstanbul)
39, 4 s. res.